The swine market movement and structure in Mexico: Implications for animal welfare and environmental impact. - Nicolás Callejas-Juárez; Francisco Ernesto Martínez-Castañeda; Nathaniel Alec Rogers-Montoya; Elein Hernandez (PLoS ONE)
The aim of this study was to analyze the evolution of Mexico's swine movement network over a five-year period (2017-2021), using a network approach to examine the significant implications of pig movement on animal welfare and environmental impact. Swine-movement records used were obtained from the Servicio Nacional de Sanidad, Inocuidad y Calidad Agroalimentaria (SENASICA). In the period 2017-2021, 33.3 million pigs were transported each year, 87.29% of them for slaughter, 12.20% for fattening, 0.50% for breeding and 0.01% for fairs. The low density and centrality of the network resulted in high market concentration. Key states in the network were Jalisco for supply and the State of Mexico for demand, with high levels of market-information loss. The main animal welfare concern identified was associated with transport duration and conditions. Although the findings comply with current legislation on pig transport duration, future measures should target improvements in transport conditions, such as implementing resting periods and enhancing traceability.